Preface. Conference Committees (Вопросы атомной науки и техники, 2007)
This issue of the Journal PROBLEMS OF ATOMIC SCIENCE AND TECHNOLOGY
consists of two parts and contains communications presented at the 2-d International Conference
on Quantum Electrodynamics and Statistical Physics (QEDSP2006). The Conference was held in
Kharkov, Ukraine, from September 19 to September 23, 2006. It took place at the National
Science Center “Kharkov Institute of Physics and Technology” (NSC KIPT).